A Systematic Review Investigating Measurement Properties of Physiological Tests in Rugby - Chiwaridzo, M.; Oorschot, S.; Dambi, J.M.; Ferguson, G.D.; Bonney, E; Mudawarima, T.; Tadyanemhandu, C.; Smits-Engelsman, B.C.M. (BMC Sports Science, Medicine and Rehabilitation, 2017)
Background: Despite debate regarding their effectiveness, many different post-exercise recovery strategies are used by athletes. This study compared five post-exercise recovery strategies (cold water immersion, contrast water immersion, active recovery, a combined cold water immersion and active recovery and a control condition) to determine which is most effective for subsequent short-term performance and perceived recovery. Methods: Thirty-four recreationally active males undertook a simulated team-game fatiguing circuit followed by the above recovery strategies (randomized, 1 per week). Prior to the fatiguing exercise, and at 1, 24 and 48 h post-exercise, perceptual, flexibility and performance measures were assessed. Results: Contrast water immersion significantly enhanced perceptual recovery 1 h after fatiguing exercise in comparison to active and control recovery strategies. Cold water immersion and the combined recovery produced detrimental jump power performance at 1 h compared to the control and active recovery strategies. No recovery strategy was different to the control at 24 and 48 h for either perceptual or performance variables. Conclusion: For short term perceptual recovery, contrast water therapy should be implemented and for short-term countermovement power performance an active or control recovery is desirable. At 24 and 48 h, no superior recovery strategy was detected..
Keywords: Physiological characteristics; Reliability; Responsiveness; Rugby; Systematic Review; Validity